Analysis of Improved Work Posture to Reduce Musculosceletal Disorders using the Rapid Upper Limb Assessment and Ovako Work Posture Analysis System methods (Case Study : Employees in the Warehouse of PT. AFS Maros, South Sulawesi) - Silvana Mohamad; Mohamad Ainul Fais; Ida Kusnawati Tjahjani (UNIPA PRESS, 2023)
PT. AFS is a Limited Liability Company engaged in catering services. One of the most important divisions in this field is in the warehousing department. Receiving is the place where the goods are entered, while the store is the place where the goods are stored for a period of time with reference to the expiration date of the product. Goods collection is done when receiving incoming goods, moving goods from the receptionist to the store, and when requesting goods from the production room. Body posture is a determining factor in analyzing the effectiveness of a warehouse operator's work. If the operator's work attitude is wrong or not ergonomic, the employee will tire easily and bone abnormalities can occur. Complaints of Musculoskeletal Disorders are complaints of skeletal muscles that are felt by a person from very mild to severe complaints. For the RULA and OWAS methods, posture analysis is only carried out in the main warehouse. The final Rapid Upper Body Limb Assessment (RULA) score for both workers was Score 7 (Action Level 4) which indicates that this condition is dangerous and requires immediate inspection and changes (on the spot). And the Ovako Work Posture Analysis System (OWAS) shows category 4 (This attitude is very dangerous for the musculoskeletal system. Needs to be corrected immediately/currently) and Category 1 (in this system problems in the musculoskeletal system don't need to be fixed).PT. AFS is a Limited Liability Company engaged in catering services. One of the most important divisions in this field is in the warehousing department. Receiving is the place where the goods are entered, while the store is the place where the goods are stored for a period of time with reference to the expiration date of the product. Goods collection is done when receiving incoming goods, moving goods from the receptionist to the store, and when requesting goods from the production room. Body posture is a determining factor in analyzing the effectiveness of a warehouse operator's work. If the operator's work attitude is wrong or not ergonomic, the employee will tire easily and bone abnormalities can occur. Complaints of Musculoskeletal Disorders are complaints of skeletal muscles that are felt by a person from very mild to severe complaints. For the RULA and OWAS methods, posture analysis is only carried out in the main warehouse. The final Rapid Upper Body Limb Assessment (RULA) score for both workers was Score 7 (Action Level 4) which indicates that this condition is dangerous and requires immediate inspection and changes (on the spot). And the Ovako Work Posture Analysis System (OWAS) shows category 4 (This attitude is very dangerous for the musculoskeletal system. Needs to be corrected immediately/currently) and Category 1 (in this system problems in the musculoskeletal system don't need to be fixed).